AWARENESS AND KNOWLEDGE AMONGST DENTAL PRACTITIONERS ABOUT NATAL AND NEONATAL TEETH AND ITS MANAGEMENT IN CHENNAI - A CROSS-SECTIONAL STUDY - SUSMITHA BASKAR,; DEEPA GURUNATHAN,; SHANMUGAVEL KARTHIKEYAN, (International Journal of Pharma and Bio Sciences, 2016)
This study was carried out to assess awareness, knowledge and method of management of natal and neonatal teeth amongst dental practitioners. Among 250 dentists 200 dentists from all dental specialties, across Chennai participated in this cross sectional questionnaire based study. Demographic details such as age, qualification, years of practice, specialty, type of practice and other objective oriented details such as type of teeth i.e. natal and neonatal teeth observed, and knowledge about natal and neonatal teeth and its preferred method of management were collected. We observed that out of the 200 dentists 73% of the dentists observed the natal the neonatal teeth. Around 49% of them know the most common complication and 69% are sure to refer to pediatric dentist for management. We concluded that the observation of natal and neonatal teeth was increasing among dentist and they have sufficient knowledge about the natal and neonatal teeth.